Shortcut to the Fourth Industrial Revolution: The case of Latin America. (December 2020) - Celani, Gabriela
In the fields of architecture and urban design, there has always been a delay in the impact of industrial revolution technologies, and in the case of less industrialised countries, the delay has been even bigger. This article starts with a review of the history of computer-aided architectural design in Brazil and then describes the state of the field in some Latin American countries. Finally, we discuss the 'ideal computer curriculum' for architects in the Fourth Industrial Revolution.